The Influence of Green Branding on Repurchase Decisions: A Study on Kopi Nako Daur Baur - Zakya Cahaya Kamila; Ratih Pandu Mustikasari (Indonesian Journal Publisher, 2026)
The coffee industry in Indonesia continues to grow rapidly, with more than 62,000 outlets currently operating nationwide. Amid this growth, competition is no longer confined to product quality but also involves the values a brand offers, one of which is expressed through the widely adopted concept of green branding. However, research examining the influence of this strategy on consumers' repurchase decisions remains relatively limited, particularly from the standpoint of consumers' own lived experience with a brand. This study aims to analyze the influence of green branding on repurchase decisions among customers of Kopi Nako Daur Baur, a brand that puts sustainability into practice through the use of recycled materials, the Rinse and Collect program, and the Seven Sec Action environmental campaign. The research employed a quantitative approach grounded in the Theory of Planned Behavior, involving 100 respondents selected through purposive sampling, with data analyzed using simple linear regression. The results indicate that green branding has a positive and significant effect on repurchase decisions. Descriptive analysis shows that the environmental performance satisfaction indicator received the highest score, while green attributes recall received the lowest, suggesting that consumers' actual experience with sustainability practices is more decisive for loyalty than mere recall of a brand's environmental programs. These findings indicate that green branding is most effective in driving repurchase decisions when sustainability values are communicated through consistent, tangible experience, offering theoretical grounding for TPB-based green branding research and practical direction for sustainability communication strategy in the coffee industry.